Answer:
x=-9/4, y=-27/4. (-9/4, -27/4).
Explanation:
y=7x+9
2y+2x=-18
----------------
simplify 2y+2x=-18 into y+x=-9
------------------
7x+9+x=-9
8x+9=-9
8x=-9-9
8x=-18
x=-18/8
simplify
x=-9/4
y=7(-9/4)+9=-63/4+9=-27/4
Just multiply the first equation by -1 and then add them together to find x. Should look something like
-2x - y = -7
5x + y = 9
--------------------
3x + 0 = 2
x = 2/3
Now back substitute using either equation to find y. I'll use the first:
2(2/3) + y = 7
4/3 + y = 7
y = 7 - 4/3 = 21/3 - 4/3 = 17/3
x=2/3
y=17/3
5.2m questions
6.8m answers